Tuberculosis Control in Kamphaeng Phet Hospital, from October 2004 to September 2006 - Khontong, Rotjana (Journal of Health Science of Thailand, 2017)
The World Health Organization restated global targets for tuberculosis control to treat successfully 85 percent of detected smear-positive TB cases. The objective of this study was to evaluate on case finding and cure rate of pulmonary tuberculosis in Kamphaeng Phet hospital from September 2004 to October 2006. The study revealed a total number of TB registered patients on 2004-2006 of 858 cases and reported 341 or 39.7 percent positive sputum in TB suspects mostly male 71.3 percent employed 52.5 percent aged from 13 to 85 years. The new cases of pulmonary tuberculosis (New M+) were treated with 2HRZE/4HR. The resulting were success rate 69.2 percent, conversion rate 79.2 percent, default rate 2.4 percent, failure rate 5.3 percent and death rate 12.8 percent. Generally, it showed a low cure rate. The retrieval activity was addressed through the telephone, the radio program, letter and home visit strategies of the public health station. The factors correlation of the default rate increase was related to death, absence and old age. The author suggests that the strategy indicates community participation and service activities should be strengthened among key community leaders. Health officers and village health volunteers have to supple adequate care and enough medicine to new patients.